Building muscle and performance a program for size, strength & speed - Tumminello, Nick (Champaign, IL Human Kinetics, 2016)
Muscle & Performance offers a unique approach to specialized training that results in improved sport performance through increased strength, power, speed, agility, and endurance, while sculpting a lean and muscular physique. Readers will learn how to get a body that looks and works great.
Functional-Spectrum muscle training -- Building muscle, increasing strength -- Cardio conditioning -- Upper Body-Pushing -- Upper Body-Pulling -- Lower body -- Core -- Warm-Up and Cool-Down -- Foundational Programming -- Performance Programming -- Muscle Programming -- Performance and Muscle Programming -- Customizing programs for personal results.
Includes bibliographical references and index.
Keywords: Weight training; Muscle strength; Speed; Physical fitness -- Physiological aspects